The Investment Nature of Unit-linked Life Insurance - Jedynak, Tomasz (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2015)
The paper considers the issue of unit-linked life insurance, and seeks to verify two hypotheses: that unit-linked life insurance products available on the Polish market have an investment character, and that their main purpose is to multiply invested capital. The study was based on a detailed analysis of the General Terms and Conditions of Insurance, a review of the market of unit-linked life insurance with a particular emphasis on the insurers' marketing communication and available statistics. It was found that there was no basis to reject the hypotheses, which means that the unit-linked life insurance products in the Polish market represent an alternative form of investment to those offered by other financial institutions. It was also found that the protective part in these products is marginal, and the aim of isolating it is strictly for the legal classification of certain products like unit-linked life insurance.